1969
DOI: 10.4141/cjss69-016
|View full text |Cite
|
Sign up to set email alerts
|

The Manganese Status of Some Alberta Soils

Abstract: Four A{n fractions r,"." d",.r-i*TtJt"f$", of fi ',e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1973
1973
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The availability of Mn to plants is related to a number of soil factors including soil type (Reid and Webster 1969;Semb and @ien 1970), microflora (Timonin 1950 ppm and 2l%o below 30 ppm Mn in leaf tissue (Fig. 2) Gallagher and Walsh (1943), Welsh et al (1953), Nyborg (1970 …”
mentioning
confidence: 99%
“…The availability of Mn to plants is related to a number of soil factors including soil type (Reid and Webster 1969;Semb and @ien 1970), microflora (Timonin 1950 ppm and 2l%o below 30 ppm Mn in leaf tissue (Fig. 2) Gallagher and Walsh (1943), Welsh et al (1953), Nyborg (1970 …”
mentioning
confidence: 99%
“…Recent reviews have shown Mn deficiency to be rare in the tropics (67,69), but it may be more widespread than the reviews indicate and could become more common as agricultural development proceeds. Increased incidence of Mn and other micronutrient deficiencies have been reported elsewhere with the intensification of agriculture and the introduction of new crops and high yielding cultivars (118,121).…”
Section: Discussionmentioning
confidence: 99%
“…Labanauskas (74) apparently considered this list to be applicable worldwide, and he added sandy acid mineral soils low in native Mn. In the USA, Mn deficiency is widespread on reclaimed calcareous soils, peats and mucks around the Great Lakes, and poorly drained coarse textured soils on the Atlantic Coastal Plains (73), and similar soil types have been identified with the disorder in Canada (121).…”
Section: 1 Soil Distributionmentioning
confidence: 99%
“…Leeper (1935Leeper ( , 1947 reported that a measurement of Mn within the manganous-manganic equilibrium in the soil was a more reliable indication of the capacity of the soil to supply plant requirements. Leeper (Leeper 1947;Reid and Webster 1969). EDTA-extractable Mn has also been employed as an index of available Mn (Browman et al 1970) For personal use only.…”
Section: Introductionmentioning
confidence: 99%